(untitled) (Journal of Enam Medical College, 2012)
Infantile colic is a distressing condition in infants, pathogenesis of which is still not clear. Several treatment strategies have been attempted before, but only some of them proven successful. The aim of this paper is to review studies on treatment options for infantile colic. For this, a systematic literature review was done on studies regarding pathophysiology, medical and conventional interventions for infantile colic from 1954 to March 2011. Forty nine articles included in Cochrane database were reviewed. Fourteen studies on pathophysiology and risk factors, 7 studies on effect of infantlie colic on parents and family,19 studies on management, 5 studies on other related factors and 4 literature reviews were included for review. Pathophysiology has been described in various ways in different studies and yet not conclusive. Regarding studies on management, simethicone could not significantly control colic, dicyclomine hydrochloride had serious side effects and cimetropium bromide results were favourable, but milder side effects were noted. Some nutritional studies reported low-allergen maternal diets in breastfed infants but suitability of these methods are questionable in Bangladesh. Behavioural studies on the use of decreased stimulation and contingent music were favourable in some studies. Mixed herbal tea and probiotic like Lactobacillus reuteri studies showed encouraging results. There are some scientific evidences to support a low-allergen maternal diet in breastfed infants with infantile colic. Some encouraging results exist for mixed herbal tea, cimetropium bromide and probiotics. DOI: http://dx.doi.org/10.3329/jemc.v2i1.11927 J Enam Med Col 2012; 2(1): 33-39